INCUMPLIMIENTO DEL PRINCIPIO CONSTITUCIONAL DE PROPORCIONALIDAD AL ESTABLECER LA PENA PARA EL DELITO DE FRAUDE ELECTORAL COMETIDO POR LOS SERVIDORES PÚBLICOS ESTABLECIDO EN EL ARTÍCULO 334 DEL CÓDIGO ORGÁNICO INTEGRAL PENAL - SOLÓRZANO SALINAS, PABLO SAÚL (2016)
The Constitution of the Republic of Ecuador orders the application of the principle of proportionality in the moment of draw the laws up, specifically when they imply sanctions to infractions, for that reason, if the principle of proportionality is applied into the Constitutional Norm, it would produce a positive result in the penalty case to give the appropriate sanction to the respective infraction taking into consideration the premise which if a protected legal utility is superior, the sanction will be greater for who break this utility and vice versa, without forgetting that the penalty must have the duty to rehabilitate. In the Penalty Integral Organic Code, in the article 334 is registered the crime of electoral fraud, which if it is committed by a public employee, several penalties will be applied, therefore it can appreciate that there is a lack of implementation of the Constitutional Principle of Proportionality. To understand the problem of study broadly some concepts are established and developed, such as the electoral fraud and others which do not have a specific definition but rather it must study the terminology, its history and the context in which they are applied to establish definitions and own concepts. The doctrinaires suggest which penalties should be imposed with the due proportion of the case, for instance Robert Alexy remarks that it will become 6 when possibilities exist both in the law as the current reality; On the other hand, Cesare Beccaria emphasizes on the suitable proportion which it must exist between the penalty and the infringement and also mentions the individualization of the penalty for each crime, then it would commit a serious error to sanction in a general form; writers do enough emphasis on the existing relationship between the principle of proportionality, fundamental laws and the Constitution, it relation is based on the application of principles to protect laws and they are found in a Norm, in this case on the Constitution. In the Compared Law is establish one relationship among laws of different countries and the Ecuadorian Penalty Integral Organic Code, thus they can be to found the differences that exist in both, the sanctions are raised in relation to the penalty of the German Penalty Code; for instance, in that context the analysis of the compared legislation is developed through reviews of Penalty types, comparing and drawing brief conclusions of laws which are put in relation. The compliance is given to the proposed objectives, studying the principle of proportionality in detail, the doctrine that supports this principle as its legal field, it becomes with the crime of electoral fraud; finally the technique of the survey as the support of Laws Professional which understand the studied problem statement, was used to acquire results which they help to complement the achievement of objectives where it performs a proposal of legal reform based on the decrease of the imposed penalty to the Public 7 employee, proposal that has a solid legal base and doctrinaire, that it supported specifically and fundamentally by the Constitution of the Republic of Ecuador and the Penalty Integral Organic Code